Gendered Rural Spaces - Piret Koosa (Journal of Ethnology and Folkloristics)
Book review for the publication Gendered Rural Spaces. Studia Fennica. Ethnologica 12. Edited by Pia Olsson and Helena Ruotsala. Helsinki: Finnish Literature Society 2009, 158 pages.